Research Evaluation: Unraveling the Metrics-Driven Pressures - Kulczycki, Emanuel (International Higher Education, 2023)
Metrics-based research evaluation, with origins in Russia and the Soviet Union, continues to impact scientific publication practices. The prevalence of publication counting prompts researchers to engage in adaptive behaviors, known as the “evaluation game,” with the primary motivation of preserving their standing. A shift in focus from individual achievements to collective societal needs is required, ensuring that the application of metrics aligns with the overarching goals, values, and beliefs of the academic community.